Interstitial Duplication on Chromosome 3p14.3p13 in an Adolescent with Dysmorphic Features and Autism, Case Report. (9th November 2022) - Abdelwahed, M; Jackson, R; Yurtsever, N; Singh, R; Trunca, C; Dompreh, R; Herman, C; Cohen, N; Simotas, C; Rousseau-pierre, T
Abstract: Introduction/Objective: The genetic etiology of autism spectrum disorders is only partially understood. Here we describe a 16-year-old male diagnosed with autism at two years of age. He has dysmorphic features, severe cognitive disability, and history of cryptorchidism. A review of systems was significant for slightly coarse features overall, with deep-set eyes, pinched nasal bridge with wide nasal tip, and widely spaced teeth. A large pectus excavatum deformity was also noted. Although the parent's genetic testing concluded that this likely represents de novo mutation, it is worth mentioning that our patient has a 13-year-old female maternal first cousin with learning difficulties that were said to be less severe. There is no other family history of autism. Methods/Case Report: Chromosome analysis showed an abnormal karyotype identifying a duplication of the short arm of chromosome 3 from p13 to p14.3, 46, XY, dup(3)(p13p14.3). Additional microarray testing confirmed this duplication and defined the size as 14.9 Mb. Regions of homozygosity of 29.8 Mb were also identified, representing about 1% of the autosomal genome. The duplicated area includes over 70 genes, thirteen of which are known Mendelian disease genes (IL17RD, HESX1, APPL1, FLNB, DNASEIL3, PDHB, ACOX2, ATXN7, SLC25A26, EOGT, LMOD3, MITF, and FOXP1). Duplications of 3p are extremely rare and can be de novo or inherited from a parent with a balanced translocation. Individuals with these better-described chromosome 3p duplications typically present with intellectual and developmental disabilities, such as autism, as 3p duplications typically present with intellectual and developmental disabilities, such as autism and distinctive dysmorphic features. This duplication has never been reported as a known syndrome and has minimal overlap with copy number variants (CNVs) among healthy individuals. Results (if a Case Study enter NA): NA Conclusion: Autism spectrum disorders are largely characterized by speech, communication, and social impairment of varying degrees. Diagnosis is typically made on clinical grounds, but in 14-35% of cases, a genetic basis for the disorder, typically either due to a single gene disorder or a chromosomal deletion/duplication, may be found. This case report describes a rare finding of a 14.9 Mb interstitial duplication on chromosome 3p.